Mediating identity, 'mobile-ising' culture : the social impact of MXIt in the relational lives of teens - Van der Linde, Keith (Centre for Film and Media Studies, 2015)
The primary aim of the study was to examine the mediating role that MXit plays in the identity formation of 16-18 year old adolescents. Little is known about the social impact of MXit on adolescents’ identities when this usage is so deeply embedded in the relational exchanges of teens’ everyday experiences. Nine focus groups, four group interviews and two one on one interviews were employed across six schools located in four socioeconomically divergent Cape Town suburbs demarcated using middle to upper-income (Milnerton and Newlands) and lower-income (Khayelitsha and Cloetesville) operational definitions.